O que é que tem de realmente importante lá em Chapada dos Negros, além da cicatriz? Processos de enquadramento do patrimônio, estereotipagem e silenciamento de memórias em Arraias-TO - Nolasco, Genilson Rosa Severino (2022)
This thesis is the result of research carried out in Arraias, a city located in the southeast region of Tocantins. Its base goal was to understand how the people of Arraias have appropriated the physical traits (FERRAZ, 1997) associated with the colonial past and the enslavement of black people, regarding special attention to the Chapada dos Negros’ ruins. I sought to understand not only the heritage assets, the Chapada dos Negros’ ruins, but mainly how things become or have become heritage in that locality, at the same time that I problematized the limits of heritage public policies. Therefore, the investigative approach was developed through two movements, as Pollack (1989) suggests. Firstly, a “from top to the bottom” movement involving an ethnography of the State’s heritage process and its agents. Second movement was the “from the bottom to the top” view, in which I’ve looked for the subjects’ ethnography, their point of view and enunciation places.